An Air Map of the Heart of St. Mary's City - First Capital of Maryland and Birthplace of Religious Freedom in America - H. C. Forman, J. Spence Howard (Henry Chandlee Forman, 1965)
An aerial view of the area of St. Mary's City, with annotations showing the probable locations of various early buildings. Also shows names of early tracts (freeholds) and their owners.